Communication behaviours of children with cerebral palsy who are minimally verbal. (8th July 2020) - Mei, Cristina; Fern, Bethany; Reilly, Sheena; Hodgson, Madeleine; Reddihough, Dinah; Mensah, Fiona; Morgan, Angela
Abstract: Background: There is a lack of population‐based studies exploring the communicative behaviours of minimally verbal children with cerebral palsy (CP), with factors associated with superior and poorer communication outcomes unknown. This study aimed to examine the communication behaviours of minimally verbal children with CP recruited from a representative community sample and to identify factors associated with communication outcomes. Methods: Twenty minimally verbal children aged 5–6 years, recruited through the Victorian Cerebral Palsy Register, completed the Communication and Symbolic Behaviour Scales–Developmental Profile (CSBS‐DP). Linear regressions examined child‐related and environmental factors associated with communication outcomes. Results: CSBS‐DP total raw scores ranged from 0 to 113. Strengths were the use of conventional gestures and understanding of language. Challenges were noted in using sequential action schemes during play. Communication typically served to regulate the behaviour of others. All participants demonstrated reduced functional communication (Communication Function Classification System levels III–IV). In the multivariable regression model adjusted for cognition, poorer communication skills were associated with Manual Ability Classification System levels IV–V ( P = 0.004). Conclusions: Although some children with CP who are minimally verbal use a variety of communication functions, significant functional limitations may be apparent. Severe upper limb impairment may provide an early indication of greater communication difficulties.